2019
DOI: 10.1021/acs.est.9b06135
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Chemistry Has a Greater Influence on the Mobility of Nanoparticles Used for Remediation than the Chemical Heterogeneity of Aquifer Media

Abstract: The application of nanoscale zerovalent iron (nano-ZVI) particles for groundwater remediation has spurred research into the influence of the collector heterogeneity on the nano-ZVI mobility. The chemical heterogeneity of surfaces within aquifer media affects their surface charge distribution and their affinity for nano-ZVI. The groundwater chemistry affects the properties of both aquifer surfaces and the nano-ZVI particles. Commercial poly­(acrylic acid)-coated nano-ZVI (PAA–nano-ZVI) particles were tested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Laboratory tests and field trials have, however, demonstrated that there are still some obstacles to address in order to reach the full potential of the nZVI technology. These include (i) low electron efficiency of nZVI and (ii) rapid particle agglomeration and sedimentation. , These limitations reduce the particle reactivity, longevity, and mobility in the subsurface. …”
Section: Introductionmentioning
confidence: 99%
“…Laboratory tests and field trials have, however, demonstrated that there are still some obstacles to address in order to reach the full potential of the nZVI technology. These include (i) low electron efficiency of nZVI and (ii) rapid particle agglomeration and sedimentation. , These limitations reduce the particle reactivity, longevity, and mobility in the subsurface. …”
Section: Introductionmentioning
confidence: 99%
“…Processes such as homoaggregation (i.e., aggregation of ENMs of the same nature) and heteroaggregation (i.e., the aggregation between non-homologous particles), which are dependent on the chemistry of the receiving environmental media (i.e., soil, freshwater and saline) and on the NP functional coatings, may limit their ability to be internalized by the cells as well as their dissolution capabilities [119,120]. On the other hand, processes such as resuspension and disaggregation, luckily occurring in natural water bodies (river, estuaries and oceans) could still make bioavailable a consistent fraction of ENMs to aquatic organisms along the water column or in sediments [121]. Similarly, processes such as oxidation, sulfidation, chlorination and dissolution, more frequent for metal-based ENMs, could significantly affect their environmental behavior and toxicity [29].…”
Section: Environmental Safety Of Enmsmentioning
confidence: 99%
“…in the field. 1,2 There is an intimate interaction between ENMs and surfaces of solids in porous media such as soils, important to quantify for risk assessment, because it determines both bioavailability of the ENMs to soil organisms and potential transport to aquifers sometimes used for drinking water production. Transport prediction of ENMs in soils is also important for ENMs intentionally added to porous media, such as nanopesticides or nanozerovalent iron used in groundwater remediation.…”
Section: Introductionmentioning
confidence: 99%